Trademark Ownership by the Local Government of the Special Region of Yogyakarta: A Model for Municipal Ownership of Intellectual Property Rights - Budi Agus Riswandi (Faculty of Law, Jambi University, 2020)
This article aims at elaborating the trademark ownership by the local government in Yogyakarta. As an effort to leverage the region’s historical status in order to add value to products made in this region, the Special Region of Yogyakarta (the “DIY” or the “DIY Government”) has registered its trademarks like “Jogjamark” and “100% Jogja.” However, there remains a question as to wether the DIY Government have the same rights and obligations concerning intellectual property as private entities, as longa a municipal government is concerned. Generally, a public legal entity is subject to the same laws, with both rights and obligations, as any other legal entity. In this context, the local government of the DIY’s registration of these marks clearly confirms that the Local Government of the DIY is the trademark owner of those trademarks. This registration requires the question as to whether this government entity can legally own registered trademarks or not. In addition, even if the registration is legal, to what extent can the local government use and protect its intellectual property? This paper will address these two issues through an empirical research study, and determines that as a legal entity, the local government can and should own trademarks for the benefit of its population.